Implementation of Primary Health Care theory in Stunting Prevention by Social Workers and Health Workers: A Case Study in Malang Regency - Hutri Agustino; Khadijah Alavi; Aizan Sofia Amin; Zahara Abdul Manaf (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: This research aims to analyse the role of social workers and health workers in stunting prevention in Malang Regency, East Java, based on the theory of Primary Health Care (PHC). Data from the Central Bureau of Statistics shows that stunting in East Java Province has a frequency of 23.5 per cent, with 14 cities above the average and 24 cities below the provincial average. Malang District itself is below the average frequency with a percentage of 25.7 per cent. Therefore, Malang District is one of the priorities in stunting prevention. Methods: This research used a descriptive qualitative approach. The analysis was thematic and the data was interpreted by identifying, analyzing, and reporting patterns or themes that emerged in the data. Informants in this study consisted of social workers from the Family Hope Program (PKH) and social rehabilitation assistants from the Ministry of Social Affairs. Meanwhile, health workers came from the Indonesian Midwives Association (IBI) in Malang Regency and Public Health Centres (Puskesmas) from four subdistricts, namely Sumberpucung, Kromengan, Wonosari, and Ngajum. The total number of informants was 12 people. This research has been approved by the Ethics Secretariat of the National University of Malaysia (UKM) with reference number: JEP-2023-928. Results: The results of this study indicate that stunting is not only viewed from a health perspective but also from a socio-economic perspective. In line with the Primary Health Care (PHC) theory, the role of social workers focuses on preventive, promotive, and rehabilitative activities that encompass social services and economic empowerment. These activities are carried out by social workers in their roles as educators, facilitators, and social advocates. Meanwhile, healthcare workers carry out curative activities that focus on medical interventions in their role as guides. Collaboration between social workers and healthcare workers is crucial in the process of preventing stunting in Malang Regency to achieve more optimal results. Conclusion: In the perspective of Primary Health Care (PHC) theory, the role of social workers in stunting prevention in Malang District focuses more on the implementation of promotive, preventive, and rehabilitative roles - while for professions in the health sector focuses more on the role of physical healing or recovery (curative). This has implications for interprofessional collaborative activities in stunting prevention to be more effective and efficient.